Enriching English-Malay proverbs using proverbs card game for second language learners / Zawani Badri ... [et al.] - Badri, Zawani; Amat, Rafidah; Abd Rahim, Mas Aida (Universiti Teknologi MARA, Kedah, 2021)
For ESL students, acquiring English proverbs have always been a struggle due to a wide range of aspects related to L2 that are mostly dissimilar with their L1. However, many studies conducted have accentuated the significance of comprehending L2 proverbs in encouraging students' communicative competence in real-life context. Due to limited L2 exposure or knowledge related to proverbial texts, ESL students have the tendency to use word-for-word translation when they attempt to use them in writing and speaking. To encourage students to use suitable English proverbs, a 52-piece proverbs card game that consists of English proverbs with equivalent Malay proverbs pairs was introduced to 20 heterogeneous level of ESL diploma students. A case study with a predominant quantitative method was employed where the preliminary pre- and post-test were conducted to investigate the significance of introducing the proverbs card game to reduce students' direct translation. Subsequently, the result was later validated with qualitative data where semi-structured interviews were conducted in order to identify the affective variables as proposed by Krashen (1982) in Affective Filter Hypothesis. From the findings, it can be presumed that there is a significant difference between pre- and post-test scores with the post-test scores being higher than the pre-test scores. Moreover, based on the hypothesis, data analysed from the semi-structured interviews revealed respondents' affective variables such as motivation, self-confidence, attitude were high and anxiety are high, thus, it allows more comprehensible input when they were playing with the proverbs card game. Therefore, it can be concluded that teaching L2 proverbs using card game can help students' reduce dependency on direct translation and lower their affective filter hypothesis which enriches their usage of L2 proverbs.